Cognitive Ageing in Bidialectalism - Antoniou, Kyriakos; Petinou, Kakia (My University, 2023)
There is some evidence—though controversial—that speaking two languages (bilingualism) or two dialects of the same language (bidialectalism) enhances executive control [1]—a set of attention and memory-related processes, such as working memory (WM) and switching [2]. Bilingualism is thought to enhance EC because bilinguals presumably use EC on a constant basis during everyday communication in order to manage their simultaneously active languages in the mind and brain [1]. Executive control (EC) declines with advanced age [3]. Importantly, the positive bilingual effects have been argued to mitigate cognitive deterioration with ageing and to delay neurodegenerative diseases, such as dementia [4]. In this work, we present preliminary results from research examining bidialectalism as an experience that potentially preserves EC in older adults. Thirty-one Greek-speaking bidialectal (in Cypriot and Standard Modern Greek) older adults (>50 years old) were given the Number-Letter (NL) [e.g., 5] and Color-Shape (CS) switching tasks [e.g., 6]; and the Forward and Backward Corsi WM task [e.g., 7]. Their EC was compared to 50 multilingual (in Cypriot, Standard Modern Greek, and other languages), 78 bidialectal, and 51 monolingual (in Standard Modern Greek) young adults (<50 years old) from previous work, which showed some evidence for a multilingual and bidialectal EC benefit. From switching tasks, we used the mixing cost (reaction-time difference between repeat trials in mixed and repeat trials in pure blocks), which consistently shows lower performance in older than young adults [e.g., 8]. We formed composite scores from related variables by averaging relevant z-transformed measures (in parentheses): Mixing (reverse-scored mixing costs in NL and CS tasks) and WM (forward and backward score in Corsi). We predicted that bidialectal older adults will exhibit less EC decline compared to monolingual than compared to mutltilingual and bidialectal young adults. An Analysis of Variance with Group and EC as factors showed a significant Group effect (F(3, 206)=2.75, p<.05): older bidialectals had lower overall EC than younger multilinguals (contrast estimate=0.34, SE=0.15, p<.05) and bidialectals (contrast estimate=0.3, SE=0.14, p<.05) but not than monolinguals (estimate=0.1, SE=0.15, p<.05). We consider the possibility that bidialectalism mitigates ageing-related EC decline, in the context of the limitations of this investigation at this stage (e.g., the absence of a monolingual older adult comparison group).